IMPLEMENTASI TEKNOLOGI PENYIRAMAN TANAMAN TEMBAKAU OTOMATIS BERBASIS INTERNET OF THINGS (IOT) DENGAN METODE FUZZY MAMDANI - Nurcahyono, Bagus; Heru Mujianto , Ahmad; Mufarrihah , Iftitaahul; Ali , Mahrus (Fakultas Teknologi Informasi, 2025)
The development of modern technology plays a crucial role in enhancing efficiency and societal well-being. The demand for efficient and energy-saving automatic tools is increasing, both in industry and households. Plant growth heavily depends on environmental parameters such as temperature and soil moisture, which must align with the plant's needs. In Lamongrejo Village, tobacco farmers still use manual irrigation methods, which are time-consuming, labor-intensive, and inefficient in water usage, thus decreasing the interest of young generations in agriculture. This research aims to design and test an IoT (Internet of Things)-based automatic plant irrigation system using the fuzzy Mamdani method. This system employs soil moisture and temperature sensors to monitor soil conditions in real-time, which are then processed using the fuzzy Mamdani method to regulate the water volume. The research findings indicate that the soil moisture sensor and DHT-11 function effectively, categorizing soil conditions into very good, good, poor, and bad, and automatically adjusting the irrigation volume accordingly. Irrigation is scheduled automatically every day at 3:00 PM with the help of an RTC module. Using this system makes it possible to increase irrigation efficiency, conserve resources, and attract the interest of young generations in agriculture. Keywords: Internet of Things, fuzzy Mamdani, automatic irrigation, soil moisture sensor, agriculture .